2020
DOI: 10.1155/2020/8631258
|View full text |Cite
|
Sign up to set email alerts
|

Increment of Lysosomal Biogenesis by Combined Extracts of Gum Arabic, Parsley, and Corn Silk: A Reparative Mechanism in Mice Renal Cells

Abstract: Gum Arabic (GA), parsley, and corn silk have been traditionally used for renal failure patients worldwide. This study aimed at probing the mechanism of the combined extracts, namely, GA (3 g/kg/day), parsley (1 g/kg/day), and corn silk (200 mg/kg/day), as nephroprotective agents in mice after amikacin (1.2 g/kg) single dose through exploration of their action on G-protein coupled receptors (GPR) 41 and 43 and the ensuing lysosomal biogenesis. Western blotting was employed for renal levels of bcl-2-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…Helmy et al (2020) agreed with this result and revealed that AK 1.2 g/kg single intraperitoneal injection increased expression of BAX in renal tissue.Aminoglycosides can cause apoptosis in the kidney by increasing the content of cytosolic Bax protein, which leads to activating the mitochondrial pathway of apoptosis, it includes caspase 9 activation as an initiator, caspase 3 activation as an effector and DNase activation, resulting in DNA fragmentation and apoptosis(Servais et al 2006).In this study, EA 10mg/kg orally one hour before AK reduced the expression of BAX in renal tissue Sepand et al (2016). agreed with this nding and reported that EA 10mg/kg decreased gentamycin-induced nephrotoxicity in rats by increasing Bcl2/BAX ratio and decreasing Caspase-3.…”
supporting
confidence: 88%
“…Helmy et al (2020) agreed with this result and revealed that AK 1.2 g/kg single intraperitoneal injection increased expression of BAX in renal tissue.Aminoglycosides can cause apoptosis in the kidney by increasing the content of cytosolic Bax protein, which leads to activating the mitochondrial pathway of apoptosis, it includes caspase 9 activation as an initiator, caspase 3 activation as an effector and DNase activation, resulting in DNA fragmentation and apoptosis(Servais et al 2006).In this study, EA 10mg/kg orally one hour before AK reduced the expression of BAX in renal tissue Sepand et al (2016). agreed with this nding and reported that EA 10mg/kg decreased gentamycin-induced nephrotoxicity in rats by increasing Bcl2/BAX ratio and decreasing Caspase-3.…”
supporting
confidence: 88%
“…Helmy et al . (2020) agreed with this result and showed that AK 1.2 g/kg single intraperitoneal injection increased BAX expression in renal tissue [ 28 ].…”
Section: Discussionsupporting
confidence: 63%
“…3 Imperatorin is another furanocoumarins identified in parsley. 22,28 In addition, rosmarinic acid, which is a polyphenolic compound, constitutes the major ingredient in the aqueous extract of parsley leaves, as this showed the largest peak in a HPLC chromatogram of the extract. 16 The study also provided a sugar profile of the aqueous extract in which sucrose, glucose, rhaminose, mannose, arabinose, and mannitol were identified.…”
Section: ■ Indigenous Traditional Knowledgementioning
confidence: 99%
“…crispum )) reported apigenin and kaempferol glycosides to be widely detectable in all evaluated samples . Additionally, luteolin and several of its structurally related derivatives such as cinaroside and chrysoeriol have be isolated from different parts of the plant. , Hesperidin and its aglycone hesperetin, naringin and its aglycone naringenin, and isorhamnetin (3-methylquercetin) are other flavonoids isolated mostly from the aerial parts of parsley (Table ). Because flavonoids are generally soluble in polar organic solvents such as methanol and ethanol, these solvents, individually or mixed with different proportions of water, seem to be the most suitable choices for the extraction of these compounds from the plant material.…”
Section: Chemistry Of Parsleymentioning
confidence: 99%